Effect of Nutrient Management on Population Growth of Brown Planthopper, Nilaparvata lugens (Stål) (Bangladesh Rice Journal, 2014)
Brown planthopper (BPH), Nilaparvata lugens (Stål) is a major insect pest of rice in Bangladesh. Nutrient management in rice received little attention on BPH population. The present study evaluated the consequences of nitrogen (N), phosphorus (P) and potassium (K) application on population build up and weight of BPH in the laboratory and net-house at Entomology Division, Bangladesh Rice Research Institute. Three levels of soil nitrogen (0, 100, 200 kg N ha-1), phosphorus (0, 20, 40 kg P2O5 ha-1) and potassium (0, 60, 120 kg K2O ha-1) were compared for individual and combined effects. Interactions of N, P and K demonstrated no significant effect on population growth and weight of BPH. However, interaction of N and P showed significant effect on population growth of BPH. Fertilization with nitrogen increased population and dry weight of BPH. Phosphorus fertilization markedly increased the population growth while high potassium application decreased population build up and dry weight of BPH.DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20900Bangladesh Rice j. 2013, 17(1&2): 38-48